The effect of adding Bi3+ on the performance of a newly developed iron–copper redox flow battery. Issue 16 (23rd February 2018) - Kabtamu, Daniel Manaye; Lin, Guan-Yi; Chang, Yu-Chung; Chen, Hsueh-Yu; Huang, Hsin-Chih; Hsu, Ning-Yih; Chou, Yi-Sin; Wei, Hwa-Jou; Wang, Chen-Hao
Abstract : In this paper, we propose a new, abundant, cost-effective, non-toxic, and environmentally benign iron–copper redox flow battery (Fe/Cu RFB), which employs Fe 2+ /Fe 3+ and Cu + /Cu 0 as the positive and negative electrolytes, respectively. Abstract : In this paper, we propose a new, abundant, cost-effective, non-toxic, and environmentally benign iron–copper redox flow battery (Fe/Cu RFB), which employs Fe 2+ /Fe 3+ and Cu + /Cu 0 as the positive and negative electrolytes, respectively. The effect of graphite felt (GF) electrode modification and addition of Bi 3+ into the electrolytes on the performance of the Fe/Cu RFB were investigated. It was found that the cell containing Bi 3+ in the electrolytes revealed higher coulombic efficiency (89.18%) and energy efficiency (35.24%) than the cell without Bi 3+ (CE = 84.10% and EE = 34.43%) at 20 mA cm −2 . This is because after adding Bi 3+, Cu metal precipitation was not observed on the electrode surface, which indicates that the deposition process was potentially reversible on the electrode material, thus leading to enhanced performance of the battery. Furthermore, the efficiencies of the battery are stable over 10 cycles, which demonstrates that Fe/Cu RFB exhibits good stability on the microwave heat treated GF plus one layer microwave heat treated carbon paper (HT-GF + HT-CP) electrode after adding Bi 3+ into the electrolytes.